Interaction mechanism of water movement and gas desorption during spontaneous imbibition in gas-bearing coal. (15th June 2022) - Yue, Jiwei; Wang, Zhaofeng; Shi, Biming; Dong, Jiaxin; Shen, Xiaojing
Highlights: The greater the gas pressure around the capillary with one end opening, the more obvious the plugging effect. A multi-branched capillary bundle model is established. The lower the gas pressure, the better the wetting effect on the micropores and some mesopores. Spontaneous imbibition can be used as a supplementary measure to promote gas drainage. Abstract: After a series of permeability enhancement and gas drainage measures are implemented in low permeability coal seams, the gas content still does not up to national standard. How to improve the transformation rate from adsorbed gas to free gas is very important. Coal seam water injection is a comprehensive disaster prevention measure. The flowing of water includes the processes of seepage and spontaneous imbibition during coal seam water injection. The process of seepage mainly displaces free gas, which shows the characteristics of rapid attenuation. The gas and water interact with each other during spontaneous imbibition which is an important way of water movement to the depth of coal seam. Spontaneous imbibition is the key to fully wetting, which provides guarantee for the water distribution in coal seam, and which establishes the foundation for the replacement of adsorbed gas. In this paper, a device integrated the isobaric water addition, isobaric desorption and spontaneous imbibition height measurement was developed. Isobaric desorption can ensure that the replaced gas is quantitatively tested. The change of electrical resistivity was grouped into the processes of sudden change, fast change and gradual change. The spontaneous imbibition height increases with increasing gas pressures during isobaric imbibition. Based on dimensionless analysis method, the mechanism that the greater the gas pressure around the capillary with one end opening, the more obvious the plugging effect is revealed. The lower the gas pressure, the better the wetting effect on the micropores and some mesopores. The equilibrium state of micropores and some mesopores determines whether the process of spontaneous imbibition is over. This study realizes the recognition of coal seam water injection technology.